Primary Hepatic Actinomycosis - Cetinkaya, Ziya; Kocakoc, Ercan; Coskun, Serdar; Ozercan, Ibrahim Hanefi (Karger, 2010)
Objectives: To present a case of primary hepatic actinomycosis. Clinical Presentation: A-40-year-old man was admitted to the general surgery clinic with a 1-month history of abdominal pain and weight loss. Liver transaminase, bilirubin levels and white blood cell counts were increased. Abdominal ultrasound and CT revealed cystic lesions with necrotic debris involving the posterior segment of the right lobe of the liver and the medial segment of the left lobe. Intervention: The patient underwent surgery under general anesthesia. On exploration, three cavities were found within the liver containing necrotic material. Surgical debridement and drainage was performed. Histopathological examination revealed actinomycotic colonies with a surrounding suppurative granulomatous reaction. The patient was treated with penicillin for 3 months. Conclusion: This case showed that histological examination of biopsy or surgical material or anaerobic cultures was needed for definitive diagnosis and that hepatic actinomycosis should be included in the differential diagnosis of solitary or multiple hypodense liver lesions. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Actinomycoses; Liver; Computed tomography